A study of the flood events in Cyprus - K. Savvidou; K. A. Nicolaides; S. C. Michaelides; A. Orphanou; M. Charalambous; S. Adamou (Advances in Science and Research, 2008)
Almost every year, localised and in some cases more widespread floodings affect parts of Cyprus, causing damages to properties destruction to infrastructure and housing and sometimes the loss of human life. Various factors such as the meteorological situation and type and intensity of precipitation, the geomorphology, the geology and the human intervention to geomorphology are responsible for flood events. In the present study, only the meteorological situation and the associated mechanisms are examined in an attempt to gain the essential knowledge for improvement of local weather forecasts. The study period covers a thirteen-year period, from 1994 to 2006, in which 43 cases of flooding were reported, mainly over urbanized areas. The dominant favorable weather conditions for flood events are either the existence of a depression or weather conditions of convectional type. According to these two factors, the flood events were classified into two categories; the "instability'' category which includes isolated flood events of short duration, and the "depression'' category which includes widespread flood events of long duration.